Maintaining the Quality of Higher Education Graduates Based on Risk Management - Akhmad Arif Rifan; Mhd. Lailan Arqam; Djamaluddin Perawironegoro (Al-Hayat: Journal of Islamic Education, 2022)
The graduates as the scholarly outputs are the key features managing the department of higher education. The department's graduation success is by fulfilling the expected graduation criteria, including education, research, and community service. This research aimed to study the efforts of the department to maintain the quality of the graduates by implementing a risk management approach. The research methods used were qualitative and quantitative, used collectively. The data was collected by interview, observation, documentation, and questionnaires; then, data analysis was carried out using inductive and descriptive quantitative data analysis techniques. The study was conducted in the magister Islamic studies program of Universitas Ahmad Dahlan Yogyakarta. Data were obtained from the department managers, which included 57 active students out of 87 students while the research was conducted in progress. The research results show that qualified graduates who meet graduation criteria are the risk the department faces. The efforts to maintain student graduation were achieved by a risk management approach and the steps of risk identification, risk assessment, risk placement, risk reviewing, and reporting. Risk management contributed to minimizing the risk of ungraduated students. Moreover, a risk management approach becomes necessary to prevent failure to achieve the planned quality objectives.